Las habilidades blandas y su influencia en el desempeño de los docentes de la universidad laica Eloy Alfaro de Manabí Ext. Chone - Bazurto Muñoz, Jenniffer Juliana (2024)
The objective of the research was to analyze the influence of soft skills on the job performance of teachers at the Universidad Laica Eloy Alfaro de Manabí Ext. Chone, in order to improve educational quality. A descriptive, field and bibliographic methodology was used, divided into three phases. In the first stage, the teachers' soft skills were evaluated using a structured survey with a Likert scale, validated by Rodríguez (2020), and its internal consistency was determined using Cronbach's Alpha. In the second phase, the relationship between the study variables was analyzed with the Spearman test, after verifying the normality of the data with the Kolmogórov-Smirnov test. In the third phase, strategies were proposed to strengthen soft skills in job performance, using a 5W+1H planning matrix, which was shared with the competent authorities of the institution. The findings revealed deficiencies in key areas such as responsibility, adaptation, communication, disciplinary mastery, didactic mastery, classroom management, and motivation and self-efficacy. It is concluded that strengthening soft skills contributes significantly to improving teacher performance, as statistical correlations showed positive and strong trends.